2001
DOI: 10.1097/00007435-200101000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Screening Program for Chlamydial Infection in Incarcerated Adolescents

Abstract: The authors instituted a screening program for chlamydial infection in incarcerated youth that was performing well at reassessment 6 months later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…These rates are comparable to those found in the YPiCHS, 3 except for much higher gonorrhoea positivity amongst females in the US study, likely reflecting the higher community prevalence of gonococcal infections in some US populations. A higher prevalence of gonorrhoea and chlamydia infections have been found among females in several overseas incarcerated juvenile populations 27,39,40 suggesting that where resources are limited, targeted screening of females may be a more cost-effective intervention. Reactive syphilis serology occurred in 0.7-1.9% of females and 0.2-1.4% of males.…”
Section: Sti/bbv Prevalence Data From Overseasmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates are comparable to those found in the YPiCHS, 3 except for much higher gonorrhoea positivity amongst females in the US study, likely reflecting the higher community prevalence of gonococcal infections in some US populations. A higher prevalence of gonorrhoea and chlamydia infections have been found among females in several overseas incarcerated juvenile populations 27,39,40 suggesting that where resources are limited, targeted screening of females may be a more cost-effective intervention. Reactive syphilis serology occurred in 0.7-1.9% of females and 0.2-1.4% of males.…”
Section: Sti/bbv Prevalence Data From Overseasmentioning
confidence: 99%
“…13,15,38 These have proven to be highly sensitive, 15 acceptable to incarcerated youth, 39 and for chlamydial infections, cost-effective 43 and practical in the juvenile correctional setting. 40 Self-collected specimens result in improved access to screening for this population, as many young adults find clinician-collected specimens unacceptable. 39 Many juveniles will only be admitted to detention facilities for short periods of time and thus admission screening using rapid in-house tests are recommended overseas.…”
Section: New Technology For Sti Screeningmentioning
confidence: 99%
“…Young age (< 30 years) and reported condom use with a casual partner were independent predictors of a chlamydia infection in that study [88]. Others have also reported high prevalences for chlamydia in incarcerated men, especially adolescents, but have not separated the prevalence by presence or absence of symptoms [82,83,85]. Since men in detention have been found to practice high-risk behaviors that put them at risk for STDs, screening of this population has been recommended as a worthwhile public health intervention of compelling need [84].…”
Section: Multiple Pathogens and Alternative/ New Testing Venuesmentioning
confidence: 93%
“…There have been few studies of chlamydia and gonorrhea in incarcerated women or men in the United States [82-85,86•]. One such study in adolescents reported a prevalence of 28.1% in girls and 9.6% in boys [85]. Most detention facilities throughout the United States test for genital infections on the basis of symptoms, but testing of asymptomatic persons is highly desirable, since STDs are often asymptomatic.…”
Section: Multiple Pathogens and Alternative/ New Testing Venuesmentioning
confidence: 99%
“…We found in previous research that the prevalence of chlamydia infection in this population is approximately 25%. 1,4 Adolescents who complained of lower abdominal pain either on or after admission had a pelvic examination by one of two experienced clinicians (the same ones who examined patients in the previous study) to assess for possible PID. If these examiners made a diagnosis of PID, the patients received, in addition to urine chlamydia screening, a cervical test for gonorrhea and chlamydia (Gen-Probe Pace 2C and Pace 2 Assays), as well as saline and potassium hydroxide wet preparations of vaginal mucus, a pregnancy test, urine culture, complete blood count with differential, erythrocyte sedimentation rate, HIV test, and RPR.…”
Section: Methodsmentioning
confidence: 99%